Online collaborative note-taking strategies to foster EFL beginners' literacy development. (August 2015) - Yang, Yu-Fen; Lin, Yuan-Yu
Abstract: This study investigated the effects of online collaborative note-taking strategies on English as a Foreign Language (EFL) beginners' literacy development. Fifty-two EFL beginners enrolled in literacy instruction to learn how to read texts (up to 350 words) and write the main ideas by using collaborative note-taking strategies. They were separated into a control group ( N = 26), which received paper-based instruction, and an experimental group ( N = 26), which received online instruction. The results indicate that the EFL beginners in the experimental group made greater progress than those in the control group as they actively utilized the online collaborative note-taking strategies available to comprehend the texts, and more particularly, in clarifying and reflecting on their own and their peers' reading and writing difficulties. In contrast, the beginners in the control group had few or no opportunities to collaborate with peers in sharing notes, nor did they explicitly observe their peers' learning process by checking log files, or save peers' important words, leading to little literacy improvement. Online collaborative note-taking strategies facilitate EFL beginners' literacy development to construct new language knowledge through text decoding (note-taking), text encoding (writing main ideas), and text discussion (collaborative interaction).